2008
DOI: 10.1016/j.fertnstert.2007.10.080
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to ovarian reserve testing

Abstract: Objective-To critically examine ovarian reserve testing prior to assisted reproduction. Design-A PUBMED computer search to identify relevant literature. Setting-Multiple sites Interventions-Testing for ovarian reserve Main Outcome Measures-IVF and pregnancy outcomesResult(s)-The prevalence of ovarian insufficiency varies significantly for women aged 30-45 years. Generalization or averaging of threshold values across different aged women leads to very poor sensitivity, specificity, and positive predictive value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…It has been suggested that diminished ovarian reserve in younger women may be more reflective of quantity, rather than quality of oocytes [4,14,15]. Abdalla et al [14] demonstrated that although younger cycling patients with high FSH had significantly lower number of oocytes collected and lower number of available and transferred embryos, their pregnancy rate was significantly higher than older women with normal FSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that diminished ovarian reserve in younger women may be more reflective of quantity, rather than quality of oocytes [4,14,15]. Abdalla et al [14] demonstrated that although younger cycling patients with high FSH had significantly lower number of oocytes collected and lower number of available and transferred embryos, their pregnancy rate was significantly higher than older women with normal FSH.…”
Section: Discussionmentioning
confidence: 99%
“…They may continue to be otherwise asymptomatic for several more years and they have been classified as "early ovarian ageing" [2]. It is necessary to distinguish this separate group of patients from the physiologic ovarian ageing for proper interpretation of ovarian reserve screening tests and altering stimulation regimens [4].…”
Section: Introductionmentioning
confidence: 99%
“…These have included: early-follicular-phase blood values of FSH and estradiol, antral follicle counts (AFCs); inhibin B levels in serum and follicular fluid, and anti-Müllerian hormone (AMH) levels [42,43]. Although some studies have demonstrated these factors to be associated with oocyte quantity [44,45], some but not all have been associated with oocyte quality and fertilization potential [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that her risk of DOR varies directly with increasing age. Therefore, we regard the age-related type of DOR as physiologic DOR [20]. Other causes of DOR, such as autoimmune and idiopathic, will be superimposed on this physiologic DOR and may thus be considered pathologic DOR, because they reflect abnormal ovarian aging [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we regard the age-related type of DOR as physiologic DOR [20]. Other causes of DOR, such as autoimmune and idiopathic, will be superimposed on this physiologic DOR and may thus be considered pathologic DOR, because they reflect abnormal ovarian aging [20]. Stated differently, pathologic DOR reflects a process that accelerates the normal physiologic decline in ovarian function with age.…”
Section: Introductionmentioning
confidence: 99%